EKSISTENSI ORANG MELAYU KAMPAR DI PROVINSI RIAU STUDI KASUS: WILAYAH LIMO KOTO KABUPATEN KAMPAR - Ali, Muhamat; Melay, Ridwan; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to find out the origin of the Malay community of Limo Koto, Kampar. Data was collected using an interview approach with respondents who are niniak mamak Limo Koto, Kampar. Based on the results of research conducted by researchers, researchers can conclude that the existence of society. Kampar has indeed existed since the 7th century during the Srivijaya Kingdom, this is evidenced by the inheritance of the Muara Takus Temple. Along with the development of the era began to stand Pagaruyung Kingdom in 1347 M. Then the Kingdom of Pagaruyung spread the influence of its culture until it reached the current Kampar region and the area of Kampar Regency gained cultural influence from West Sumatra. The reason why the people of Kampar do not want to be said by the Minang people is because Kampar and Minang are the names of a place, where the place is an identity of the locals. Kampar and Minang have a lot in common but because of the separation during the PRRI period that made both of them separate administratively and made the two regions claim the origin of each. Kampar residents are Minangkabau people who often refer to themselves as Ughang Ocu, scattered in most areas of Kampar with Domo tribes, Malayu, Piliong / Piliang, Mandailiong, Putopang, Caniago, Kampai, Bendang, etc. In history, ethnicity, customs, and culture they are very close to the Minangkabau people, especially with the Luhak Limopuluah area. This happened because the Kampar area was separated from the Minang Territory since the Japanese occupation in 1942. According to H. Takahashi in his book Japan and Eastern Asia, 1953. The Kaigun Military Government in Sumatra included Kampar into Riau Shio territory as part of a military territorial defense strategy on the East coast of SumatraKeywords: Existence, Malays